2017
DOI: 10.14742/ajet.3508
|View full text |Cite
|
Sign up to set email alerts
|

Examining the validity of the technological pedagogical content knowledge (TPACK) framework for preservice chemistry teachers

Abstract: While various quantitative measures for assessing teachers' technological pedagogical content knowledge (TPACK) have developed rapidly, few studies to date have comprehensively validated the structure of TPACK through various criteria of validity especially for content specific areas. In this paper, we examined how the TPACK survey measure is aligned with the TPACK lesson plan measure and how they are related to the measure of epistemological beliefs about chemistry. The participants were 280 Chinese preservic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 31 publications
(75 reference statements)
2
34
0
7
Order By: Relevance
“…The science teachers' TPACK data was measured using 45 multiple choice test questions. The question indicators were made based on TPACK for 21 st Century Skills instrument (TPACK-21) (Valtonen et al, 2018(Valtonen et al, , 2017 and TPACK survey for Meaningful Learning (Chai et al, 2011;Deng, Chai, So, Qian, & Chen, 2017;Koh, Chai, & Tsai, 2013). The development of this instrument was adjusted to science content and the integration of technology in pedagogically meaningful ways that are by the twenty-first-century skills framework (21 st -century skills framework) (Valtonen et al, 2017).…”
Section: Instrumentsmentioning
confidence: 99%
“…The science teachers' TPACK data was measured using 45 multiple choice test questions. The question indicators were made based on TPACK for 21 st Century Skills instrument (TPACK-21) (Valtonen et al, 2018(Valtonen et al, , 2017 and TPACK survey for Meaningful Learning (Chai et al, 2011;Deng, Chai, So, Qian, & Chen, 2017;Koh, Chai, & Tsai, 2013). The development of this instrument was adjusted to science content and the integration of technology in pedagogically meaningful ways that are by the twenty-first-century skills framework (21 st -century skills framework) (Valtonen et al, 2017).…”
Section: Instrumentsmentioning
confidence: 99%
“…Although the empirical research based on Mishra and Koehler's (2006) TPACK model has analysed different disciplines, including experimental sciences (Deng, Chai, So, Qian, & Chen, 2017;Jang & Tsai, 2013) or mathematics (Karatas, Piskin Tunc, Yilmaz, & Karaci, 2017), social studies has only been examined by less than 3% of recent studies (Willermark, 2018). This is something that has also affected the assessment of the integration of the digital competence of educators in initial teacher training.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Further analyses need to be carried out to validate the adapted instrument to asses for its reliability and validity before any worthwhile interpretations can be made from its use. It was reported that a TPACK version used with chemistry teacher trainees showed four types of validity which are convergent, discriminant, factorial and predictive validities (Feng, Chai, So, Qian, & Chen, 2017). Feng et al (2017) carried out both exploratory and confirmatory factor analyses as well as a factorial analysis on gender to come out with the results.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…It was reported that a TPACK version used with chemistry teacher trainees showed four types of validity which are convergent, discriminant, factorial and predictive validities (Feng, Chai, So, Qian, & Chen, 2017). Feng et al (2017) carried out both exploratory and confirmatory factor analyses as well as a factorial analysis on gender to come out with the results. The next step for this study is to carry out similar analyses on the final version of the instrument above.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%